Kerkeberade: Het dit "n plek in die Gereformeerde kerkregering? - Kleynhans, E. P. J. (Hervormde teologiese studies, 1992)
Church conferences: Does the Reformed Church government have room for it? The National Conference of Church Leaders in South Africa, held at Rustenburg in 1990, like the Cottesloe Conference in December 1960, caused a violent reaction, especially amongst members of the Dutch Reformed Church. As a matter of fact, a considerable number of members resigned in protest against what happened at Rustenburg. The question of whether such a conference could fit in with the principles of Reformed Ecclesiastical government came strongly to the fore. This question is dealt with in the article.